2018
DOI: 10.3390/f9100646
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure, Genetic Diversity, and Gene Introgression of Two Closely Related Walnuts (Juglans regia and J. sigillata) in Southwestern China Revealed by EST-SSR Markers

Abstract: The common walnut (Juglans regia L.) and iron walnut (J. sigillata Dode) are well-known economically important species cultivated for their edible nuts, high-quality wood, and medicinal properties and display a sympatric distribution in southwestern China. However, detailed research on the genetic diversity and introgression of these two closely related walnut species, especially in southwestern China, are lacking. In this study, we analyzed a total of 506 individuals from 28 populations of J. regia and J. sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…The migration from ES to SS was significantly greater than that in the reverse direction. Consistent with this result, a high asymmetric historical gene flow was detected among these two species, which occurred predominantly from J. regia into J. sigillata [52]. Based on the above results, we suggest that the walnuts in Sichuan province were likely derived from the North China population.…”
Section: Linkage Disequilibrium and Migration Rate Estimationsupporting
confidence: 80%
See 1 more Smart Citation
“…The migration from ES to SS was significantly greater than that in the reverse direction. Consistent with this result, a high asymmetric historical gene flow was detected among these two species, which occurred predominantly from J. regia into J. sigillata [52]. Based on the above results, we suggest that the walnuts in Sichuan province were likely derived from the North China population.…”
Section: Linkage Disequilibrium and Migration Rate Estimationsupporting
confidence: 80%
“…The walnut perhaps survived the last glaciations in some refugia, and all the modern distribution probably was affected by humans [51]. Some previous studies also suggested that J. regia and J. sigillata should be considered as a single species, and J. sigillata might be an ecotype of J. regia [42,52]. So further research could uncover more information about the phylogenetic relationships among them.…”
Section: Linkage Disequilibrium and Migration Rate Estimationmentioning
confidence: 99%
“…The genomic mosaicism of both the Persian walnut (incl. J. sigillata) and the American butternut J. cinerea provides evidence for the importance of hybridization throughout the evolution of walnuts, matching (Bai et al 2016;Yuan et al 2018;Zhao et al 2018). However, our results from the entire genus, which today is most species-rich in North and South America while Europe has a single species (supplementary fig.…”
Section: Discussionmentioning
confidence: 55%
“…EST-SSR markers have been extensively used in the study of genetic diversity and population structure because of several advantages over studies of noncoding nuclear genomes, such as increased transferability to related species [37], increased accuracy when accessing differences in adaptation among populations [38], increased amplification success, conserved primer sites and a simplified analysis [39]. However, even though whole-genome sequencing has been completed [1], only a few EST-SSR markers have been developed in earlier studies [9,16,20], and a number of polymorphic and informative EST-SSR markers in particular are still lacking.…”
Section: Development Of Est-ssr Markers For C Camphoramentioning
confidence: 99%